Diwali - Amin, Anita Nahta (2022)
"Diwali is about celebrating! It honors the Hindu story of Rama. Sikhs, Buddhists, and Jains also celebrate Diwali. To celebrate this Festival of Lights, people light lamps, watch fireworks, and dance. Others might exchange cards and presents. Readers will discover how a shared holiday can have multiple traditions and be celebrated in all sorts of ways"--
Includes bibliographical references and index.
Ages 5-8
Grades K-1
Keywords: Divali -- Juvenile literature